2019
DOI: 10.1002/adom.201901446
|View full text |Cite
|
Sign up to set email alerts
|

Broadband CrOCl Saturable Absorber with a Spectral Region Extension to 10.6 µm

Abstract: Many studies have focused on NLO materials that are used in highpower pulsed lasers in the ultraviolet, visible, and near-infrared (IR) spectral ranges. Constrained by the currently available mid-IR NLO materials, mid-IR pulsed lasers with a wavelength range from 2.5 to 20 µm are underdeveloped. [5,6] NLO materials with saturable absorption properties are often used as the SAs of passively Q-switched lasers and modelocked lasers. Saturable absorption is one kind of NLO effect induced by the imaginary part of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 65 publications
0
15
0
1
Order By: Relevance
“…Q-switched bulk lasers can be developed by combining BP SA with Pr:GdLiF 4 , Nd:GdVO 4 , and Tm:Ho:YGG laser at 639 nm, 1.06 μm, and 2.1 μm. [252] The recent studies also have reported the adoption of various anisotropic 2D materials, including Ta 2 NiS 5 , [253] Ta 2 NiSe 5 , [254] ReS 2 , [255] CrOCl, [256] and PdSe 2 [257] as the SA of bulk lasers for ultrafast pulse generation. However, the polarized laser pulse generation has yet to be achieved in bulk laser with 2D SAs since the fabrication of single-crystalline 2D SAs large enough to cover the beam radius of the bulk laser remains a challenge.…”
Section: Polarized Lasersmentioning
confidence: 99%
“…Q-switched bulk lasers can be developed by combining BP SA with Pr:GdLiF 4 , Nd:GdVO 4 , and Tm:Ho:YGG laser at 639 nm, 1.06 μm, and 2.1 μm. [252] The recent studies also have reported the adoption of various anisotropic 2D materials, including Ta 2 NiS 5 , [253] Ta 2 NiSe 5 , [254] ReS 2 , [255] CrOCl, [256] and PdSe 2 [257] as the SA of bulk lasers for ultrafast pulse generation. However, the polarized laser pulse generation has yet to be achieved in bulk laser with 2D SAs since the fabrication of single-crystalline 2D SAs large enough to cover the beam radius of the bulk laser remains a challenge.…”
Section: Polarized Lasersmentioning
confidence: 99%
“…CrOCl has recently been reported as a promising air-stable vdW antiferromagnetic (AFM) insulator. , The neutron scattering studies describe the magnetic ground state of CrOCl as an unconventional SDW along the b -axis with an easy axis of the c -axis, that is, a stripy- y AFM order. As the temperature decreases, CrOCl first transforms from a paramagnetic state into an incommensurate SDW state at ∼27 K ( T mag ), then into a commensurate state with an SDW wavelength of 4 b ( b is the lattice constant) at the Néel temperature of ∼14 K. Both neutron scattering , and X-ray diffraction (XRD) results show that the magnetic phase transition at Néel temperature is accompanied by a structural phase transition from orthorhombic space group Pmmn to monoclinic space group P 2 1 / m , indicating sizable magnetoelastic coupling in CrOCl.…”
Section: Introductionmentioning
confidence: 99%
“…Although exploring broadband saturable absorbers (SAs) has been a research hotspot in recent decade, few SAs have been proved to be effective in deep mid-infrared . So far, commercial semiconductor saturable mirrors (SESAMs) have been the most mature SAs, but their working wavelengths are limited below ∼3 μm wavelength .…”
mentioning
confidence: 99%
“…Although exploring broadband saturable absorbers (SAs) has been a research hotspot in recent decade, few SAs have been proved to be effective in deep mid-infrared. 27 commercial semiconductor saturable mirrors (SESAMs) have been the most mature SAs, but their working wavelengths are limited below ∼3 μm wavelength. 28 The investigations of lowdimensional materials including carbon nanotubes, graphene, topological insulators, transition metal dichalcogenides (TMDs), and black phosphorus (BP) have aroused wide interests due to their broadband optical responses.…”
mentioning
confidence: 99%